A Statement for a New Era: The Association for Institutional Research Statement of Ethical Principles. Issue 183 (26th May 2020) - Appel, Michelle S.
Abstract: This chapter begins with an overview of the history of the Association for Institutional Research's use of ethical guidelines. The Association reworked these principles during 2019, the next chapter discusses the rationale and process for this rework. Next, AIR's new Statement of Ethical Principles is presented and discussed, and finally the chapter closes with a discussion of next steps.